2003
DOI: 10.1152/ajpregu.00058.2003
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-type differences in muscle mitochondrial profiles

Abstract: Although striated muscles differ in mitochondrial content, the extent of fiber-type specific mitochondrial specializations is not well known. To address this issue, we compared mitochondrial structural and functional properties in red muscle (RM), white muscle (WM), and cardiac muscle of rainbow trout. Overall preservation of the basic relationships between oxidative phosphorylation complexes among fiber types was confirmed by kinetic analyses, immunoblotting of native holoproteins, and spectroscopic measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 41 publications
4
73
0
Order By: Relevance
“…The concentrations of cytochromes a, b, c 1 and c from the electron transport chain were quantified by difference spectra according to Leary et al (Leary et al, 2003). Six hundred micrograms of mitochondrial proteins (40μl of mitochondrial suspension) were diluted in 960μl of phosphate buffer (NaH 2 PO 4 and Na 2 HPO 4 50mmoll −1 pH7.8 at 25°C) without Triton-X.…”
Section: Cytochrome Concentrationsmentioning
confidence: 99%
“…The concentrations of cytochromes a, b, c 1 and c from the electron transport chain were quantified by difference spectra according to Leary et al (Leary et al, 2003). Six hundred micrograms of mitochondrial proteins (40μl of mitochondrial suspension) were diluted in 960μl of phosphate buffer (NaH 2 PO 4 and Na 2 HPO 4 50mmoll −1 pH7.8 at 25°C) without Triton-X.…”
Section: Cytochrome Concentrationsmentioning
confidence: 99%
“…Fatty acid oxidation was assayed using a modified protocol for human skeletal muscle (Bezaire et al 2006) and respiration buffer for fish (Leary et al 2003). Palmitate oxidation was determined at room temperature by measuring trapped 14 C from labeled CO 2 production after a 30-min incubation of viable mitochondria in a sealed system.…”
Section: Enzyme and Protein Assaysmentioning
confidence: 99%
“…Mitochondria are centers of aerobic metabolism that generate the bulk of ATP needed to maintain cellular functions based on a highly organized catabolic system consisting of the tricarboxylic acid (TCA) cycle, fatty acid import by the carnitine palmitoyltransferase (CPT) system, and downstream β-oxidation and electron-transferring pathways. Several recent studies have shown that depending on the respiratory capacity of the muscle, specific mitochondrial phenotypes exist in metabolically different muscle fibers in several vertebrates, such as pigs, rats, and rainbow trout (Glancy and Balaban, 2011;Leary et al, 2003;Picard et al, 2012;Ponsot et al, 2005).…”
Section: Introductionmentioning
confidence: 99%